On the distribution of the time of the first exit from an interval and the value of a jump over the boundary for processes with independent increments and random walks - Kadankov, V. F.; Kadankova, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
For a homogeneous process with independent increments, we determine the integral transforms of the joint distribution of the first-exit time from an interval and the value of a jump of a process over the boundary at exit time and the joint distribution of the supremum, infimum, and value of the process.